2011
DOI: 10.1007/s11426-011-4290-2
|View full text |Cite
|
Sign up to set email alerts
|

Ln2MO4 cathode materials for solid oxide fuel cells

Abstract: One of the major challenges to develop "intermediate temperature" solid oxide fuel cells is finding a novel cathode material, which can meet the following requirements: (1) high electronic conductivity; (2) chemical compatibility with the electrolyte; (3) a matched thermal expansion coefficient (TEC); (4) stability in a wide range of oxygen partial pressure; and (5) high catalytic activity for the oxygen reduction reaction (ORR). In this short review, a survey of these requirements for K 2 NiF 4 -type material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 71 publications
(79 reference statements)
0
44
0
Order By: Relevance
“…Using mass relaxation technique it was possible to simultaneously evaluate D and K in 600-900 8C temperature range. Activation energy of D was calculated to be 0.13 (2) eV. Results of chemical stability studies in relation to Ce 0.8 Gd 0.2 O 1.9 electrolyte revealed moderately good chemical compatibility of Pr 2 CuO 4 oxide, while La 2 CuO 4 and Nd 2 CuO 4 stability proved to be insufficient.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Using mass relaxation technique it was possible to simultaneously evaluate D and K in 600-900 8C temperature range. Activation energy of D was calculated to be 0.13 (2) eV. Results of chemical stability studies in relation to Ce 0.8 Gd 0.2 O 1.9 electrolyte revealed moderately good chemical compatibility of Pr 2 CuO 4 oxide, while La 2 CuO 4 and Nd 2 CuO 4 stability proved to be insufficient.…”
mentioning
confidence: 92%
“…High temperature XRD data revealed anisotropic thermal expansion of Pr 2 CuO 4 , smaller along c-axis. Based on reduction experiments performed on TG apparatus, the initial slight oxygen excess d present in the compounds at room temperature was evaluated: La 2 CuO 4.03 (2) , Pr 2 CuO 4.05 (2) and Nd 2 CuO 4.04 (2) . Additionally, it was observed that up to 900 8C in air the oxygen content in the materials does not change considerably.…”
mentioning
confidence: 99%
“…Most of the compounds with K 2 NiF 4 structure have the ability to accommodate large amount of M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 interstitial oxygen ions or generate loss of oxygen vacancies. These advantages make Ln 2 MO 4 as good candidates as cathodes for SOFCs [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, only La 0.6 Sr 1.4 MnO 4 was reported to be a promise anode for SOFCs [28] and potential symmetrical electrode for SSOFCs [29] which showed a maximum power density of 59 mW cm -2 at 800 0 C (H 2 as a fuel).…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned above oxide compositions have potential to be used in microelectronics, catalysis and sensor technology [1][2][3][4]. Most of the rare-earth elements form only RNiO3 compositions.…”
Section: Introductionmentioning
confidence: 99%